Macroeconomic announcements, communication and order flow on the Hungarian foreign exchange market - Michael Frömmel; Norbert Kiss M.; Klára Pintér (Magyar Nemzeti Bank, 2009)
We investigate the relation between the EUR/HUF exchange rate on the one hand and news announcements and order flow on the other hand using intraday data. We extend the existing literature on foreign exchange market microstructure by considering a small open transition economy. We find that the intraday exchange rate - independent from whether we focus on the mean or the volatility - depends on both news announcements and order flow. We conclude that news on the EUR/HUF market are transmitted directly via immediate reactions to news announcements as well as indirectly via order flow. We decompose the news' total effect on exchange rate and find that order flow accounts for approximately three quarters, compared to one quarter for direct news impact. Although the HUF has been pegged to the EUR, the exchange rate reacts qualitatively very similarly to exchange rates of major currencies as reported in the literature, but quantitatively we observe a remarkable difference: the share of the indirect channel is higher on the EUR/HUF market. Furthermore we extend the commonly used news by communication of central bankers and significantly improve the explanatory power of the regressions. Our results imply that macroeconomic and microstructure variables together can explain a non-negligible part of high frequency exchange rate movements and central bank communication is an important determinant of the EUR/HUF rate.
Keywords: F31; G14; G15; 330; microstructure; order flow; exchange rate; macroeconomic news; central bank communication; Zentralbank; Kommunikation; Staatliche Information; Ankündigungseffekt; Wechselkurs; Anlageverhalten; Devisenmarkt; Marktmikrostruktur; Ungarn